Dor orofacial e qualidade de vida de adultos - Silva, Silvio Rocha Corrêa da [UNESP]; Leite, Carla Maria Carvalho; Ferraz, Maria Ângela Arêa Leão; Silva, Moisés Franco Barbosa; Sousa, Yara Teresinha Corrêa Silva (My University, 2012)
To determine the prevalence and intensity of orofacial pain in adults that participated in a health program at Ribeirão Preto. Methodology: The study was conducted by a self-administered questionnaire, with 19 questions in 99 people aged 18 to 66 years. The method used for data collection was the index Oral Impacton Daily Performances (OIDP), which evaluated the six months preceding the survey, pain experiences in the mouth, teeth or dentures and how these factors interfere with daily activities. Statistical analysis was performed using Epi Info version 3.4. Results: The majority of the adults who participated in this survey (52.5%) reported having an excellent or good oral health, reported having problems with their teeth (60.6%), no problems with the gums (77.8%), no bad taste in mouth (77.8%) or bad breath (77.8%). Among the participants of the study, 56.6% felt orofacial pain in the last six months and the pain were more frequently caused by cold or hot liquids (30.3%), spontaneous pain (17.2%), during the mouth opening (17.2%), pain in the face (13.1%) and ATM (13.1%). Regarding the severity rate, the highest proportion varied from mild to moderate. Conclusions: Even observing a low severity of orofacial pain, its prevalence was high, which probably has a negative effect on life quality of these people.

Observar a prevalência e a intensidade da dor orofacial em adultos que participaram de uma campanha de saúde no município de Ribeirão Preto. Metodologia: o estudo foi realizado por meio da aplicação de um questionário, auto- -aplicável, com 19 questões, em 99 pessoas, na faixa etária de 18 e 66 anos. O instrumento utilizado para a coleta dos dados foi o índice Oral Impacton Daily Performances (OIDP), que avaliou, nos seis meses anteriores à pesquisa, experiências de dor na boca, dentes ou próteses e como elas interferem nas atividades diárias. Para análise estatística foi utilizado o programa Epi Info versão 3.4. Resultados: os adultos que participaram desta pesquisa, em sua maioria (52,5%), declararam ter uma saúde bucal excelente ou boa, relataram ter problemas com os dentes (60,6%), não ter problemas com a gengiva (77,8%), não ter gosto ruim na boca (77,8%) ou mau hálito (77,8%). Dos participantes do estudo, 56,6% sentiram dor orofacial nos últimos seis meses e as dores mais frequentes foram: dor provocada por líquidos frios ou quentes (30,3%), dor espontânea (17,2%), ao abrir a boca (17,2%), dor no rosto (13,1%) e na ATM (13,1%). Em relação à severidade a maior proporção observada foi de leve e moderada. Conclusões: mesmo observando uma baixa severidade da dor orofacial, sua prevalência foi alta, o que provável tem efeito negativo na qualidade de vida destas pessoas.
Orofacial pain and quality of life for adults
Keywords: Orofacial pain; Life quality; Health indicators; Dor orofacial; Qualidade de vida; Indicadores de saúde